Le factitif français: approche syntaxique, sémantique et contrastive (français-bulgare) - Novakova, Iva (Travaux neuchâtelois de linguistique, 2002)
This article proposes a comparison between the French construction faire + Vinf and the structures encoding a causative meaning in Bulgarian. The data are classified according to the scale of compactness of the Australian linguist R.M.W. Dixon. If the French uses the construction with faire (Complex Predicate), the Bulgarian uses three other mechanisms: lexical (explode), morphological (affixation: raz-plakvam, faire pleurer), periphrastic constructions with two verbs (a causative verb and a lexical verb) in separate clauses (inciter quelqu’un à faire quelque chose). This typological classification shows the correlation between syntactical and semantic parameters in the analyse of causatives. Some verbs, basically intransitive in French, can be used in a transitive clause and then take on a causative meaning (bouger la banlieue). In this case, there is a concurrence between faire + inf and the intransitive verb in transitive construction. The article attempts to clarify this usage, in comparison with other languages (English, Russian, Bulgarian), and some other specificity of the functioning of the French construction faire + Vinf.